Phytochemical studies and the bioactivities of three meliaceae species / Ibrahim A. Najmuldeen - Najmuldeen, Ibrahim A. (2011)
This thesis describes phytochemical studies on three species of Malaysian plants, Chisocheton ceramicus, Chisocheton tomentosus, and Dysoxylum macrocarpum from Meliaceae family, in which the latter two species have not been found in the literature. The present work on these plants involves extraction, isolation and purification of compounds by using column chromatography followed by preparative TLC or RPHPLC and structural elucidation, which has been done through several spectroscopic methods, notably UV, IR, MS (HRMS, GCMS, and LCMS), 1D, 2D-NMR (1H NMR, 13CNMR, COSY, DEPT, HMQC, HMBC, NOESY, and single crystal X-ray diffraction analysis. This work has resulted twenty new compounds including five limonoids while the rest were phenolic compounds, furthermore, three new compounds as crystals. In addition, twenty-six known compounds have been isolated and characterized for the first time from all of these plants. The five new isolated compounds from the bark of Chisocheton ceramicus were chisomicine A CC1, chisomicine B CC2, chisomicine C CC3, chisomicine D CC4, and chisomicine E CC5, along with 14-deoxyxyloccensin K CC6, which was new in its occurrence as natural product and as crystal. This compound has been synthesized from xyloccensin K, and one known compound, proceranolide CC7. Furthermore, fifteen new compounds, CT5A, CT5C, CT5D, CT5K, CT5L, CT5M, CT5N, CT5O, CT5P, CT6B, CT6C, CT6L, CT6M, CT6N, CT6O as well as one new as crystal, 7-hydroxy-β-sitostertol CT1 were amongst the thirty eight compounds isolated from the bark of Chisocheton tomentosus, while the rest were known compounds; stigmasta-4,6-diene-3-one CT2, stigmasterol CT3, sitosterol CT4, hydroxy acid derivatives of ferulate CT5B, CT5E, CT5F, CT5G, CT5H, CT5I, III CT5G, E-alkyl-p-coumarate CT6A, CT6D, CT6E, CT6F, CT6G, CT6H, CT6I, CT6G, CT6K, ferulaldehyde CT7, and vanillin CT8 and the last one was styryl lactone (goniothalamin) CT9. While the bark and leaves of Dysoxylum macrocarpum yielded four compounds, two compounds from the leaves; 5-hydroxy-7-methoxy-2-methyl-4Hchromen- 4-one (Eugenin) DM1, which was new as crystal and squalene DM2, while two more compounds were found from the bark; stigmasterol CT3 and sitosterol CT4. Five limonoids; chisomicine A CC1, chisomicine B CC2 and C CC3, 14- deoxyxyloccensin K CC6 and proceranolide CC7, were tested for their inhibitory activity against NO production. The results showed that only chisomicine A CC1 inhibited NO production in J774.1 dose-dependently stimulated by LPS and also showed little effect on cell viability. Three of above limonoids chisomicine A CC1, chisomicine B CC2, 14- deoxyxyloccensin K CC6 have been tested for its cytotoxic effects against 8 types of cancer cell lines; only chisomicine A CC1 showed positive results for colon (HT-29) cells. 7-Hydroxy-β- sitostertol CT1, hydroxy acid derivatives of ferulate CT5A-P, and ferulaldehyde CT7 from Chisocheton tomentosus were tested for in-vitro cytotoxicity activity against MCF7 cells. The results showed 7-hydroxy-β-sitostertol CT1 had the most potent cytotoxicity effect, the other compounds showed very weak or no cytotoxicity effect against MCF7 cells.